Keeping the beautiful game beautiful: The impact of referee team performance. - Aragão e Pina, J.; Passos, A. M.; Maynard, M.; Mathieu, J. (11th INGroup Annual Conference, 2016)
Leveraging survey data from every referee in the Portuguese top football leagues and game data for the entire 2014-2015 season, we examine the role of composition factors in shaping individual- and team-level referee performance. Analysis of data is ongoing and should provide insights on multi-level performance within this unique context.